Elevated expression of G3BP1 associates with YB1 and p‐AKT and predicts poor prognosis in nonsmall cell lung cancer patients after surgical resection. (27th September 2019) - Zheng, Hongmei; Zhan, Yuting; Zhang, Yuting; Liu, Sile; Lu, Junmi; yang, Yang; Wen, Qiuyuan; Fan, Songqing
Abstract: Purpose: G3BP1 is an RNA‐binding protein and plays roles in regulating signaling pathway. YB‐1 is a DNA/RNA binding protein encoded by YBX1 gene. Phosphorylated AKT (p‐AKT) acts as a pivotal molecule in PI3K/AKT pathway. YB‐1 drives stress granules (SGs) formation by activating G3BP1 translation under diverse conditions. SGs are involved in many different metabolic and signaling pathways which may include PI3K/AKT/mTOR. So far, there has been no report on the relationship between expression of G3BP1, p‐AKT, and YB1 and clinicopathological features/prognosis in surgically resected nonsmall cell lung cancer (NSCLC) patients. Methods: In this study, data from TCGA (The Cancer Genome Atlas) were downloaded to investigate the mRNA expression of G3BP1 and YB1 (YBX1) and their correlation in NSCLC. Also, expression of G3BP1, YB1, and p‐AKT proteins was studied using immunohistochemistry in tissue microarrays of NSCLC and in noncancerous lung tissues. Results: We found that the mRNA expression of G3BP1 and YB1 was higher in NSCLC tissues (both P <  .05), and G3BP1 was positively correlated with YB1 in mRNA level ( r  = .399, P  < .001). Also, expression of G3BP1, YB1, and p‐AKT proteins was higher in NSCLC tissues (all P  < .05). And higher expression of G3BP1 and YB1 proteins was seen in patients with clinical stage II and III compared with stage I (both P  < .05). Besides, expression of G3BP1 protein had a positive correlation with YB1 and p‐AKT (both P  < .05). Moreover, overall survival was shorter in patients with overexpression of G3BP1, YB1, and p‐AKT proteins (all P  < .05). Multivariate analysis confirmed that overexpression of G3BP1 protein was an independent poorer prognostic factor for NSCLC patients ( P  = .039). Conclusion: G3BP1 may play a crucial role in activating PI3K/AKT/mTOR pathway. G3BP1 might be served as a novel prognostic biomarker for surgically resected NSCLC patients, which afforded new insights into the study on the mechanism and therapy of NSCLC. Abstract : The overexpression of G3BP1, YB1, and p‐AKT protein was associated with clinicopathological features in NSCLC and the expression of G3BP1 had a positive correlation with YB1 and p‐AKT. G3BP1 may play a crucial role in activating PI3K/AKT/mTOR signaling pathway. G3BP1 protein might be served as a novel prognostic biomarker for NSCLC patients with surgical resection.